2015
DOI: 10.1089/apc.2014.0158
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Viral Load and CD4 Count Trends Among HIV-Infected Adults in South Carolina

Abstract: On a population level, trends in viral load (VL) and CD4 cell counts can provide a marker of infectivity and an indirect measure of retention in care. Thus, observing the trend of CD4/VL over time can provide useful information on disparities in populations across the HIV care continuum when stratified by demography. South Carolina (SC) maintains electronic records of all CD4 cell counts and HIV VL measurements reported to the state health department. We examined temporal trends in individual HIV VLs reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 30 publications
1
34
1
Order By: Relevance
“…There was a statistically significant lower viral load at time of diagnosis in the younger adult group compared to older adults, which is in contrast to several other studies showing youth had a higher VL at diagnosis. The reason for this difference is not clear but is unlikely to represent earlier diagnosis in Australian youths compared with other developed countries.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There was a statistically significant lower viral load at time of diagnosis in the younger adult group compared to older adults, which is in contrast to several other studies showing youth had a higher VL at diagnosis. The reason for this difference is not clear but is unlikely to represent earlier diagnosis in Australian youths compared with other developed countries.…”
Section: Discussioncontrasting
confidence: 99%
“…5 Adolescence (13-19 years) and young adulthood (20-24 years) are periods with significant physical, cognitive, social and psychological change, presenting a particular challenge in those with chronic diseases, such as HIV infection. While statistics regarding adolescents living with HIV worldwide are readily available, there is more limited information about young adults (aged [20][21][22][23][24], despite evidence that the brain, in particular the frontal lobe, has not fully developed until after this period 6 with consequent effects on executive and other function [7][8][9] likely to influence their interaction with the health system.…”
Section: Introductionmentioning
confidence: 99%
“…Others have observed no difference in CD4 cell count at time of HIV diagnosis comparing patients from rural and urban areas, 26-28 suggesting rural residence may not affect the timing of HIV diagnosis but rather may affect the time from HIV diagnosis to care initiation. Reasons for late care initiation among rural residents may be multifaceted.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the findings of no difference in virologic suppression at one year, another study in SC in which statewide viral load values from 2005 to 2012 were analyzed found that mean viral load decreases were significantly affected by urban versus nonurban residence with urban residents having better viral load decreases. 71 In a separate study of nonurban PLWH across 12 US states, half reported less than 100% adherence to prescribed ART in the past 7 days and 10% reported deviating from their prescription instructions at least daily. The authors reported that this is likely higher than most estimates for PLWH in urban areas.…”
Section: The Hiv Continuum Of Care In the Nonurban Contextmentioning
confidence: 99%